Braunschweig und die Reformation – regionalgeschichtliche Aspekte - Biegel, Gerd (International Dialogues on Education Journal, 2017)
This essay looks at the early Reformation movement in a small Guelphic principality from a regional historical perspective, with a view to the independent development in the city of Braunschweig. The cities were the actual locations where the spiritiual-clerical impulses which originated from Wittenberg and Luther were taken up most quickly. This „city reformation“ is characterized as a „citizen’s republicanism“ in the transition from the Middle Ages to modernity. Deciding factors in the transmission and dissemination of reformatory ideas were the increasing aphabetization in the cities, printing with its rapid spread of information as well as the concentration of educational institutions. Teachers, professors, predicants and the developing early humanistic educational bourgeoisie (patricians, trades and crafts people) were among the first municipal supporters of Luther’s doctrine. The result was an „embourgeoisement“ oft he church, or more precisely: the Reformation brought with it the communalization of church matters. Even more foundational was the change of municipal communal affairs through the Reformation. Aspects of commerce, law, and life in the „city“ community were expanded through a faith and religious community. Municipal church orders such as in Braunschweig in 1528, Hamburg in 1529, Hannover in 1530, 1533 in Nürnberg, or 1534 in Straßburg became symbols of this change. The impetus for the Reformation in the cities was mostly a bottom-up one, because it was concerned with enhanced participation in the day-to-day political process.